Design and development of a cross-sectional area sensor via impedance measurement - Xie, Tu Qiang. (2009)
The importance of the cardiac output as a measured parameter is that it can be used to evaluate the overall cardiac status in both critically ill patients and patients with suspected cardiovascular disease. Although there are several methods for determining the cardiac output, these methods do not allow for a continuous real-time measurement of the cardiac output for both steady and pulsatile blood flow. By combining the impedance measurement technique and velocity measurement technique, an alternative method of cardiac output measurement is proposed. In this method, a catheter, which comprises a cross-sectional area (CSA) sensor and a velocity sensor, and is to be inserted into artery. The product of blood velocity and vessel's cross-sectional area is the cardiac output.